Implementation Of Qur’an Based Nahwu–Sharaf Learning In Modern Islamic Boarding Schools - Putri Amber Ayu; Aminudin Aminudin (Universitas Al-Amien Prenduan, 2026)
This study examines the implementation of Qur’an-based nahwu–sharaf learning in Islamic boarding school education in response to students’ difficulties in understanding Arabic grammatical structures contextually. Existing instructional practices still predominantly emphasize rote memorization of grammatical rules, causing students to experience difficulties in applying grammatical knowledge to authentic Arabic texts. Previous studies have discussed nahwu and sharaf learning through analytical and authentic-text approaches; however, limited attention has been given to the integration of nahwu and sharaf within a Qur’an-based contextual learning framework in pesantren education. This study employed a qualitative case study design involving one Arabic language teacher, eight seventh-grade students, and three pesantren administrators at Pondok Pesantren Modern Darussalam Prabumulih. Data were collected through classroom observation, semi-structured interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the learning process was implemented through four interconnected stages: introduction of linguistic patterns through Qur’anic verses, structural analysis (i‘rab and sharaf), guided practice, and application in reading activities. The use of Qur’anic verses supported students’ engagement and facilitated contextual understanding of grammatical concepts through authentic textual interaction. This study concludes that Qur’an-based nahwu–sharaf learning functions as a contextual pedagogical process integrating authentic texts, staged analysis, and participatory classroom interaction within pesantren education. Keywords: Nahwu–Sharaf; Qur’an-Based Learning; Arabic Language Learning